Factors Influencing Consumers’ Purchase Intention towards Counterfeit products in Nawalparasi, Nepal - Parajuli, Rishi Kanta; Dumre, Lila Ballav; Rijal, Yagya Prasad (Madhyabindu Journal, 2026)
Counterfeit products are supplied by market follower organizations throughout the world, violating the rules of trade and ignoring consumerism. Nepalese people are also price sensitive and are using such products knowingly or unknowingly. Realizing this fact, the study aimed to identify whether there is any significant difference or not on purchase intention of non- deceptive counterfeit products among divergent professional groups, and influence of predictors on purchase intention of counterfeit products. Data were collected by purposively locating respondents at banks and colleges. Altogether 250 questionnaires were distributed, out of which only 200 complete responses were further processed and analyzed employing descriptive and inferential tools. Only four constructs/variables, such as price consciousness, personal gratification, social influence, and perceived risk, were taken into consideration to measure purchase intention. The ANOVA results suggest that there was no statistically significant difference in the purchase intention of counterfeit products among teachers, students, and bankers. Findings showed that personal gratification, social influence and price consciousness have a positive and significant relationship with purchase intention toward counterfeit products. However, perceived risk factors do not have a significant influence on purchase intention towards counterfeit products. This study may provide valuable insights to policymakers, academia, and the corporate sector in formulating and implementing effective rules and regulations to eradicate unethical trade and expand consumer awareness, lay the foundation for doing further research, and enhance brand value and equity.